2021
DOI: 10.3390/ijerph18020475
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Magnitude of Interlimb Asymmetries in Young Female Soccer Players: A Preliminary Study

Abstract: Although asymmetries in lower limbs have been linked with players’ performance in male soccer players, literature that has been published addressing female soccer is scarce. Thus, the aim of this study was twofold: (i) describe the asymmetries of women soccer players during jumping, change-of-direction and range-of-motion tests; and (ii) test possible relationships between asymmetries and injury risk in female soccer players. Sixteen female players (15.5 ± 1.5 years) performed a battery of fitness tests (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…ROM assessment of the lower limb joints has been previously investigated with regard to injury risk factor identification [49]. The hip and ankle ROM values reported in the present study are in agreement with those previously reported among female football professional players [42], establishing hip extension and ankle dorsiflexion with knee extended mobility at 15 • and 36 • (16.1 ± 7.6 • and 39.7 ± 15.0 • in the present study), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ROM assessment of the lower limb joints has been previously investigated with regard to injury risk factor identification [49]. The hip and ankle ROM values reported in the present study are in agreement with those previously reported among female football professional players [42], establishing hip extension and ankle dorsiflexion with knee extended mobility at 15 • and 36 • (16.1 ± 7.6 • and 39.7 ± 15.0 • in the present study), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that both the mean age (20 vs. 22 years old) and competition level (professional football) were similar between cohorts, the reported knee flexion flexibility difference may have arisen from methodological issues (i.e., timing of the evaluation or previous training load). Other investigations have reported greater ROM values among younger female football players [49], indicating that age and competitive level [50] may influence the ROM profile of athletes. Another interesting result from the present investigation came from the absence of significant limb-to-limb differences, suggesting that ROM asymmetries were not present on lower limb flexibility among the evaluated players.…”
Section: Discussionmentioning
confidence: 89%
“…To this end, the articular evaluation Range of Motion (ROM) is used to observe imbalance or asymmetries as risk factors for injury [ 4 , 5 ]. For the development of scientific research, different functional assessment tests can be identified, such as Star Excursion Balance Test (SEBT) [ 6 ], and Y-Balance Test (YBT) [ 7 ] for the lower body and Upper Quarter Y-Balance Test (UQYBT) [ 8 ] and modified-Upper Quarter Y-Balance Test (mUQYBT) [ 9 ] for the upper body.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main objectives of the use of these tests is the study of physical or physiological imbalances between different body segments, which can have a negative influence on the athlete’s performance or increase the risk of suffering an injury [ 5 ]. These physical or physiological mismatches are called asymmetries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation